Prognostic significance of serum carcinoembryonic antigen and squamous cell carcinoma antigen in patients with esophageal squamous cell carcinoma undergoing radical esophagectomy - Hu, Jia; Kuang, Pengpeng; Chen, Dongni; Chen, Youfang; Wen, Zhesheng (Translational cancer research, 2020)
It is generally believed that the preoperative serum carcinoembryonic antigen (CEA) and squamous cell carcinoma antigen (SCC-Ag) levels are independent predictors of prognosis in multiple malignant tumors. However, their predictive value in esophageal squamous cell carcinoma (ESCC) is still unknown. Therefore, the main purpose of this study is to detect the serum CEA and SCC-Ag levels of ESCC patients before operation, in order to clarify the clinical significance of them as prognostic factors. We conducted a retrospective review of 348 patients with ESCC treated by esophagectomy between February 2009 and October 2012. We Analyzed the influence of serum CEA and SCC-Ag level on prognosis. We used a receiver operating characteristic (ROC) curve to identify the serum CEA and SCC-Ag level for predicting survival. We used Log-rank test to compare survival curves, and Cox regression analysis to clarify significant prognostic factors. The cutoffs for CEA and SCC-Ag were 2.28 ng/mL and 0.75 ng/mL, respectively, Under curve area of CEA was 0.600 (95% CI: 0.541-0.660; P=0.001) and under curve area of SCC-Ag was 0.567 (95% CI: 0.507-0.628; P=0.030). According to the Kaplan-Meier curves, the overall survival rate (OS) and disease-free survival rate (DFS) of patients with CEA ≤2.28 ng/mL were higher than those with CEA >2.28 ng/mL. Meanwhile, patients with serum levels of SCC-Ag ≤0.75 ng/mL had a more favorable OS and DFS than those of patients with SCC-Ag >0.75 ng/mL. Cox regression analysis showed that the total mortality of patients with CEA >2.28 ng/mL was higher than that of patients with CEA ≤2.28 ng/mL (HR 1.76; 95% CI: 1.39-2.39; P<0.001). Additionally, SCC-Ag >0.75 ng/mL was an independent negative prognostic factor for DFS (HR 1.86; 95% CI: 1.17-2.96; P=0.009). As the nomogram showed, the survival rate of ESCC patients with high preoperative serum CEA and SCC-Ag levels was relatively low. High levels of serum CEA and SCC-Ag were independent and significant predictors of ESCC patients after surgical treatment.